Effect of Dapagliflozin on Glycemic Variability in Patients with Type 2 Diabetes under Insulin Glargine Combined with Other Oral Hypoglycemic Drugs - Menghui Luo; Xiaocen Kong; Huiying Wang; Xiaofang Zhai; Tingting Cai; Bo Ding; Yun Hu; Ting Jing; Xiaofei Su; Huiqin Li; Jianhua Ma (Journal of Diabetes Research)
Aim. To evaluate the effect of an inhibitor of sodium-glucose cotransporter 2 (SGLT-2 inhibitor, dapagliflozin) on glycemic variability in type 2 diabetes mellitus (T2D) under insulin glargine combined with oral hypoglycemic drugs, using a continuous glucose monitoring system (CGMS). Methods. This prospective, self-controlled, single-center clinical trial recruited 36 patients with T2D under combined insulin glargine and oral hypoglycemic drugs. General clinical data were collected. Fasting blood glucose (FBG), postprandial blood glucose (PBG), glycosylated hemoglobin (HbA1c), and C-peptide levels were assessed before and four weeks of dapagliflozin (10 mg per day) treatment. Blood glucose was monitored for 72 hours before and after treatment using CGMS. Results. After treatment with dapagliflozin, FBG decreased from 6.74±1.78 to 5.95±1.13 mmol/L (p<0.05); PBG decreased from 13.04±2.99 to 10.92±3.26 mmol/L (p<0.05); HbA1c decreased from 7.37±0.96% to 6.94±0.80%. The proportion of patients with HbA1c<7% increased from 27.8% to 58.3%, and the proportion of patients with HbA1c<7% and without level 2 hypoglycemia increased from 27.8% to 55.6% (p<0.05). CGMS data showed reduction of the 24 h MBG, MAGE, time-above-range (TAR, >10 mmol/L), high blood glucose index (HBGI), glucose management indicator (GMI), and incremental area under the curve of the glucose level more than 10 mmol/L (AUC>10) and an increase of time-in-range (TIR, 3.9-10 mmol/L) with treatment. Homeostasis model assessment for pancreatic beta-cell function (HOMA-beta) increased significantly with treatment (p<0.05), and fewer insulin doses were required after the treatment, without increasing in hypoglycemia and urinary tract infection. Further, a stratified analysis showed that patients with higher pretreatment HbA1c and waist-to-hip ratio (WHR) had greater improvement in glycemic control. Conclusion. Dapagliflozin may reduce blood glucose levels, ameliorate glycemic variability, and improve pancreatic beta-cell function in patients with T2D under insulin glargine combined with other oral hypoglycemic drugs, especially in those with poor glucose control and abdominal obesity.